حكم سماع دعوى المطلق إثبات مراجعته مطلقته بعد انتهاء عدتها: دراسة فقهية مقارنة - الكردي، رائد علي محمد (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنين بالقاهرة, 2013)
تناولت الدراسة موضوع حكم الشريعة الإسلامية في سماع دعوى الزوج إثبات مراجعته مطلقته بعد انتهاء عدتها دراسة فقهية مقارنة، حيث نص قانون الأحوال الشخصية الأردني في المادة الواحدة بعد المائة على اله لا تسمع عتد الإنكار دعوى المطلق إثبات مراجعته مطلقته بعد انقضاء عدتها وزواجها من غيره بمضي تسعين يومأ على الطلاق ما لم تكن الرجعة مسجلة رسمياً، فجاءت الدراسة لتبين حكم الشريعة الإسلامية في الذي ذهب إليه القانون، وقد تناولت الدراسة تعريف الرجعة في اللغة والاصطلاح، ومشروعيتها، ثم تناولت الدراسة مسألة حكم الإشهاد على الطلاق، كما تناولت الدراسة حكم إعلان الزوجة بالرجعة إذا أرجعها زوجها، ثم تناولت حكم سماع دعوى المطلق مراجعته مطلقته بعد انتهاء عدتها، وقد تم بحث هذه المسائل من الناحية الشرعية والقانونية، وخلصت الدراسة إلي أنه لا يمكن منع سماع دعوى المطلق إثبات مراجعته مطلقته بعد انتهاء عدتها، وزواجها من غيره بشكل مطلق كما ذهب إلى ذلك قانون الأحوال الشخصية الأردني، فهناك حالات يمكن فيها سماع إثبات مثل هذه النوع من الدعاوي.
this is a Comparative Fiqh study that aims to investigate the Islamic Shari'a hukom regarding the acceptance of a man's claim to prove the previous returning of his divorced wife after the end of her "Oddah", where as the legislative text, article number 101 in the Jordanian Personal Status Law stipulates that a man's claim to prove the returning to his divorced wife after the end of her "oddah" and her marriage of another man after ninety days of divorce is unacceptable if he denied it earlier unless he, previously, registers his proof officially. The study shows the Islamic Shari'a hukom in that Legislative text and defines the term "AI- Raj'a"and its legitimacy. It also studies the Hukom of having witnesses on divorce. Then, it shows the Hukom of informing the divorced wife of her "Raj'a" if her husband does that. Moreover, the research studies the acceptance of a man's claim to prove the returning to his divorced wife after the end of her "oddah" according to the Islamic Shari'a and law. \ Finally, the study suggests that it is inadmissible to refuse accepting a man's claim of proving the return of his divorced wife after the end of her "oddah" and getting married to another man as it is stipulated in the Jordanian Personal Status Law. As a result, in some cases we can accept the man's prove in this kind of claim.
Keywords: الفقة الإسلامي; اليمين (فقه إسلامي); الطلاق (فقه إسلامي)